The suspension of the Democratic Governance Facility in Uganda: the illusion of “politically smart aid” - Vandeputte, Nathan (Routledge, 2023)
In 2021, the President of Uganda suspended the “Democratic Governance Facility” (DGF), which is a European basket fund aimed at providing financial support in areas such as democracy, human rights, and rule of law. Paradoxically, the DGF had explicitly adopted a new “politically smart framework”, which is a development approach that promises to deliver aid more effectively and sustainably in contentious environments. This raises the question: what went wrong? Informed by post-development theoretical arguments and through a discursive analysis of the DGF’s implementation of this new aid framework, this paper argues that this framework itself does not allow proper understanding of what makes aid “political”; in casu that it does not allow appreciation of local viewpoints of democracy, representation, and ownership. Then, rather than improving the status quo, this paper argues in favour of making aid “political” through a fundamental reconsideration of the very substance and infrastructure of aid itself. International Bibliography of the Social Sciences (IBSS)
Keywords: Uganda; democracy support;thinking and workingpolitically; political aid; post-development